2019
DOI: 10.1111/ggi.13671
|View full text |Cite
|
Sign up to set email alerts
|

Can cognitive leisure activity prevent cognitive decline in older adults? A systematic review of intervention studies

Abstract: The aims of this systematic review were to investigate what kind of cognitive leisure activities have been used in intervention studies targeting older adults, and whether these activities improve cognitive function or inhibit cognitive decline. Based on the PRISMA declaration, we searched keywords using three electronic databases: PubMed, PsycINFO and Psy-cARTICLES. Intervention studies involving cognitive leisure activities with cognitive assessments set as outcomes were included. We regarded cognitive leisu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 47 publications
(235 reference statements)
2
35
0
Order By: Relevance
“…Therefore, our results confirm, what is reflected in a review, in which leisure activities involving brain stimulation such us: use of internet, boarding games and reading, are shown as protective to CI [30]. Moreover, it was proved that reading increases our brain connectivity in areas related to language and sensory region [31].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, our results confirm, what is reflected in a review, in which leisure activities involving brain stimulation such us: use of internet, boarding games and reading, are shown as protective to CI [30]. Moreover, it was proved that reading increases our brain connectivity in areas related to language and sensory region [31].…”
Section: Discussionsupporting
confidence: 88%
“…The public health implications from this finding are related to the importance of increasing late-life participation in leisure activities, their potential role in late-life cognition, and its benefits in people with and without cognitive impairment (52). Nevertheless, further research is needed to determine the amount of exposure, intervention period, and frequency for designing an effective intervention (53). The available research evidence suggests that it is not too late to increase physical and cognitive activity in old age (14) and policymaking for dementia primary prevention needs evidence for non-pharmacological interventions aiming to increase cognitive reserve (54).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, regarding other factors associated with SQoL and WB, the CAP did have a positive impact on mental health and perceived loneliness (both have small effect sizes). In other studies, social leisure activities have been suggested to promote relaxation (Packer, 2008), reduce anxiety (Binnie, 2010), and be associated with increased self‐reported health (Iizuka et al, 2019; Leadbetter & O’Connor, 2013). These results coincide with those obtained for the EG regarding an improvement in psychological health and SWB and PWB.…”
Section: Discussionmentioning
confidence: 99%